Goop clean beauty - Paltrow, Gwyneth, 1972- (Grand Central Life & Style, 2016)
"The ultimate beauty guide from the experts at GOOP--the trusted resource for healthy, mindful living, curated by Gwyneth Paltrow. Millions of women around the world turn to the clean-living team at GOOP for beauty advice. From nontoxic product recommendations, red carpet- (and everyday-) ready hair and makeup tutorials, to guidance on aging, acne, and antioxidants, GOOP has become the go-to resource for head-to-toe beauty. Finally, the editors of GOOP have curated their greatest tips and recommendations, favorite detox recipes, workout plans, and hair and makeup looks in one must-have guide. Featuring more than 100 gorgeous photos and extensive Q&As from GOOP's family of expert contributors, GOOP CLEAN BEAUTY will shed a definitive light on the importance of diet, sleep, exercise, and clean beauty products, while offering tactical advice for healthy, glowing skin and hair that starts from the inside out. The first curated book from the top name in clean-living, GOOP CLEAN BEAUTY is the one resource women need to feel, and look, their best every day"--